(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the association between vitamin D, Calcium, alkaline phosphatase and lipid profile in male and female subjects. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Darul-Sehat Hospital Karachi's outpatient department from July 2018 to January 2019 for a period of seven months. Materials and Methods: A total of 100 male and female individuals between the ages of 40 and 60 were chosen. Vitamin D, lipid profile, alkaline phosphatase, and calcium levels were all tested in the individuals' blood. The participants were divided into two groups: those who had adequate vitamin D levels and those who were deficient in vitamin D. Results: Total cholesterol and TGs were found to be higher in both male and female participants. Female subjects had lower LDL cholesterol, whereas male subjects had considerably higher LDL cholesterol. Serum HDL cholesterol, on the other hand, was exclusively elevated in female individuals while remaining unaltered in male respondents. Only female individuals had considerably higher serum calcium levels. Both male and female individuals had significantly higher serum alkaline phosphatase levels. Conclusion: Despite the fact that there is a negative correlation between 25 (OH) D levels and lipid profile in both male and female participants, serum vitamin D has been reported as a putative cardio-protective vitamin in female subjects via boosting HDL-C. Alkaline phosphatase levels were higher in both genders.